THE INFLUENCE OF CUSTOMER TRUST AND DECISION MAKING FROM CONSUMER TESTIMONIALS USING GONTOR'S HAJJ AND UMROH SERVICES IN THE MANAGEMENT REVIEW OF HAJJ AND UMROH GIRO - Lesmana, Meichio; Katsir, Shahibul Khairil; Rosmita, Siti Nurma; Mahdi, Atha (Multazam : Jurnal Manajemen Haji dan Umrah, 2024)
The study of consumer decisions in choosing KBIHU services is essential, considering the high need for Muslims to perform Hajj in Indonesia. Data from the 2024 population census notes that Indonesia's population reaches 281.64 million people, while the Hajj quota is limited. Although there are various Hajj and Umrah service bureaus, consumers need to be careful because of the rampant cases of fraud and illegal acts in this sector in Indonesia. Safety and trust are key factors that must be considered before consumers choose Hajj and Umrah service bureaus in their area. Factors influencing consumer decisions involve brand, quality of service, pricing, promotion, and word-of-mouth testimonials. This study aims to examine the impact of brand trust and word of mouth testimonials on consumer decisions in choosing KBIHU Gontor services. This research approach is qualitative, involving direct surveys and analysis of data from previous scientific literature.